A Rare Case of Gastric Outlet Obstruction due to Large Intramural Duodenal Hematoma Following Endotherapy for Bleeding Duodenal Ulcer in a Patient with End-stage Renal Disease - Gupta, Vineet Kumar; Soni, Ram Chandra (Journal of Digestive Endoscopy, 2017)
We report a very rare case and probably the first from India of gastric outlet obstruction due to a large intramural duodenal hematoma following combination endotherapy with hemoclipping and injection adrenaline 1:10,000 for actively bleeding duodenal ulcer in an elderly male patient with diabetes, hypertension, and end.stage renal disease on maintenance hemodialysis. The patient improved to approximately 6 weeks of conservative treatment with nasojejunal feeding.
Keywords: End-stage renal disease; gastric outlet obstruction; hemodialysis; intramural duodenal hematoma